Long-term hydroclimate variability in the sub-tropical North Atlantic and anthropogenic impacts on lake ecosystems: A case study from Flores Island, the Azores. (1st June 2022) - Richter, Nora; Russell, James M.; Amaral-Zettler, Linda; DeGroff, Wylie; Raposeiro, Pedro M.; Gonçalves, Vítor; de Boer, Erik J.; Pla-Rabes, Sergi; Hernández, Armand; Benavente, Mario; Ritter, Catarina; Sáez, Alberto; et al.
Abstract: Human land use and climate change threaten ecosystems and natural resources, particularly on remote islands such as the Azores Archipelago in the North Atlantic. Since the official Portuguese settlement of the archipelago in the 15th and 16th centuries humans have extensively modified the Azorean landscape, with invasive plants dominating the present-day vegetation and evidence of eutrophication in numerous lakes. To evaluate changes in terrestrial and aquatic ecosystems in the Azores, we developed paleoecological and paleoclimate records from Lake Funda on Flores Island that span the last millennium. Changes in precipitation amount, as recorded by hydrogen isotopes from C30 fatty acids ( δ Dwax ), suggest that the climate was relatively stable between c. 1000–1400 CE. Recent evidence of early human settlers on the Azorean islands (c. 850–1300 CE) suggests that the introduction of livestock led to an increase in primary productivity in Lake Funda and other lakes in the Azores. More depleted δ Dwax values between c. 1500–1620 CE suggest that wetter climate conditions existed during the establishment of permanent settlements on Flores Island. Landscape changes between c. 1500–1600 CE coincided with an increase in primary productivity and hypoxic conditions in the lake bottom water, signifying the eutrophication of Lake Funda. Despite reforestation efforts in the Azores in the early 20th century and shift towards drier conditions, eutrophication in Lake Funda persisted. Reforestation efforts likely reduced nutrient leaching and soil erosion in the catchment area of Lake Funda and other Azorean lakes, yet eutrophication continues to be widespread. This highlights the lasting impacts of early human settlers on Lake Funda, and the need for more active remediation efforts. Graphical abstract: Image 1 Highlights: High-resolution paleoclimate and paleoecological reconstruction from Flores Island. Multi-proxy records distinguish human impacts from climate change. Early human settlers lowered the resilience of lake ecosystems on remote islands.